Evaluating Marketing Strategy GrabFood Through Agile Marketing Capability Framework: A Case Study of XYZ Coffee - Wulan Yuniar Rahmawati; Adam Hermawan; Asep Nuryadin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The rapid growth of digital food delivery platforms has transformed marketing practices among micro and small enterprises (MSMEs), requiring greater adaptability and data-driven decision-making. This study aims to evaluate how Soulja Coffee’s digital marketing strategy on the GrabFood platform demonstrates the four dimensions of the Agile Marketing Capability (AMC) framework: adaptability, collaborative integration, continual innovation, and forecasting and monitoring of market needs. An explanatory sequential mixed-method design was employed. The quantitative phase analyzed six-month Grab Merchant Dashboard data (January–June 2025), including sales trends, advertising performance indicators such as click-through rate and return on ad spend, and promotional outcomes. The qualitative phase involved semi-structured interviews with two internal informants (a manager and a marketing staff member) to contextualize the quantitative findings. Results indicate evidence of adaptability through rapid promotional adjustments following sales declines; collaboration through routine coordination between management, marketing, and frontline staff; and innovation through dashboard-based experimentation, including the use of a discount calculator, which contributed to an increase in ROAS from 1.68 in March to 37.43 in June. Forecasting and monitoring practices were still descriptive, relying on manual dashboard review rather than predictive analysis. Overall, Soulja Coffee demonstrates early-stage marketing agility that remains operational rather than strategically institutionalized. The study extends AMC application to Indonesian micro-MSMEs, showing how informal learning, platform-provided tools, and iterative experimentation shape marketing agility under resource constraints, offering guidance for MSMEs to strengthen data-driven decision-making in platform-based commerce.